Protective Effects of Baicalein on Lipopolysaccharide-Induced AR42J PACs through Attenuation of Both Inflammation and Pyroptosis via Downregulation of miR-224-5p/PARP1 - Ming-Wei Liu; Chun-Hai Zhang; Shou-Hong Ma; De-Qiong Zhang; Li-Qiong Jiang; Yang Tan (Mediators of Inflammation)
Background. Baicalein has been used to treat inflammation-related diseases; nevertheless, its specific mechanism of action is unclear. Therefore, we examined the protective effects of baicalein on lipopolysaccharide-induced damage to AR42J pancreatic acinar cells (PACs) and determined its mechanism of action for protection. Methods. An in vitro cell model of acute pancreatitis (AP) was established using lipopolysaccharide (LPS) (1 mg/L)-induced PACs (AR42J), and the relative survival rate was determined using the 3-(4,5)-dimethylthiahiazo(-z-y1)-3,5-di-phenytetrazoliumromide (MTT) technique. Flow cytometry was applied to evaluate the apoptotic rates of AR42J PACs. The RNA and protein expression of miR-224-5p, poly ADP-ribose polymerase-1 (PARP1), nuclear transcription factor-κB65 (NF-κB65), phospho-kappa B alpha(p-IκB-α), interleukin(IL)-18R, NOD-like receptor thermal protein domain-associated protein 3 (NLRP3), gasdermin D (GSDMD), apoptosis-associated speck-like protein containing a CARD (ASC), and caspase-1 was detected based on the WB and RT-PCR assays. IL-1β, IL-6, IL-18, and TNF-α expression levels in AR42J cells were measured via ELISA method. The cell morphology was examined using the AO/EB method. Results. The experiment confirmed a significant increase in the activity of AR42J cells treated with various doses of baicalein. Moreover, IL-1β, IL-6, TNF-α, and IL-18 expression levels in AR42J cells were dramatically reduced (P <0.05), while miR-224-5p level was obviously enhanced. The protein and gene expression of PARP1, NF-κB65, p-IκB-α, IL-18R, GSDMD, ASC, NLRP3, and caspase-1 was obviously decreased (P<0.05). Apoptosis in AR42J cells was significantly reduced with significant improvement in cell morphology. Conclusion. Baicalein may significantly alleviate LPS-induced AR42J PAC damage by inhibiting the inflammatory response and pyroptosis. Its mode of action might be linked to higher miR-224-5p expression, which inhibits the PARP1/NF-κB and NLPR3/ASC/caspase-1/GSDMD pathways.